Русская поэзия, 1813-1825 - Архангельский Александр Николаевич (Классики и современники, 1990)
Экземпляры: КХ (20110722) / Инвентарный номер: 974481 / Цена: 2.50 / Сис.шифр: Р1 / Авт.знак: Р 89 / ГРНТИ: 17 / ББК: 84(2=411.2)-5я43